(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This study investigates the hydraulic justification of parameters for water-saving irrigation techniques and technologies applied in agricultural crop cultivation. The efficiency of modern drip and sprinkler irrigation systems is analyzed in terms of water conservation, hydraulic performance, and energy consumption. Hydraulic calculations were carried out using Bernoulli’s equation and Darcy–Weisbach formula to determine flow rates, pressure distribution, and head losses within irrigation networks. Field experiments were conducted on cotton, vegetable, and orchard crops under different irrigation technologies. Results demonstrated that drip irrigation reduced water losses to 10–15%, compared to 35–40% in traditional surface irrigation. Sprinkler irrigation saved up to 25–30% of water while ensuring uniform distribution. Energy consumption was reduced by 18–22% when pipe diameters and operating pressure were optimized. On average, 1000–1200 m³ of water per hectare was saved in cotton production. Additionally, water-saving technologies decreased groundwater table rise by 20–25%, reducing soil salinization risks and improving land reclamation conditions. The findings highlight the potential of water-saving technologies as an effective strategy for sustainable water resource management in irrigated agriculture